Can't you see I'm trying to help? Relationship satisfaction and the visibility and benefit of social support in type 1 diabetes. (March 2021) - Kent de Grey, Robert G.; Berg, Cynthia A.; Tracy, Eunjin L.; Kelly, Caitlin S.; Lee, Juwon; Lichtman, Michelle L.; Butner, Jonathan; Munion, A. K.; Helgeson, Vicki S.
Whether visible and invisible social support are beneficial depends on contextual factors, such as relationship satisfaction. The purpose of the present study was to examine whether differences in support provision are impactful in type 1 diabetes (T1D), which involves frequent opportunities for partners to provide support. We hypothesized that invisible support may be beneficial only when relationship satisfaction is high and also that relationship satisfaction may relate to greater visibility of provided support. We tested these hypotheses in a sample of 199 adult persons with T1D (PWD) and their spouses. Using a 14-day diary, PWD reported diabetes support from partners. Partners reported support provided. Invisible support was coded when PWD reported receiving no support, but partners reported providing it. If both PWD and their partner indicated support received/provided, the day was coded as visible support. Glucometers measured daily blood glucose. Participants reported baseline relationship satisfaction and daily positive and negative affect. Results indicated there were no main effects of support visibility on blood glucose or affect. Analyses showed invisible support was associated with lower mean blood glucose, smaller standard deviation of mean blood glucose, and lower average daily risk only when partner relationship satisfaction was high. Both spouses' greater relationship satisfaction was associated with more visible and less invisible support. The results contribute to the literature on invisible support, by indicating that it may yield beneficial outcomes primarily when partners are more satisfied. Overall, however, invisible support might occur more in less satisfied relationships.